PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA MATERI SISTEM RESPIRASI KELAS XI MIPA 2 SMA NEGERI 11 DENPASAR TAHUN PELAJARAN 2022/2023 - I Dewa Putu Juwana; Ni Kadek Yuni Pradnyani (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
The purpose of this study was to find out the application of the discovery learning learning models to improve student learning outcomes in biology on the subject of the upper secondary school respiratory system. This type of research was classroom action research which was conducted from December 2022 to February 2023. The research subjects were students of class XI MIPA 2 SMA Negeri 11 Denpasar for the 2022/2023 academic year. The object in this research is the results of students' biology learning on the cognitive aspect, with the material of the respiratory system with the discovery learning models. The implementation of the research was carried out in two cycles, each cycle consisting of two meetings with the stages of planning, action, observation, evaluation and reflection. The results showed that in cycle I, the average pre-test score for students was 59. Meanwhile, the average post-test score for students was 67.64. In cycle II, the average student pre-test score was 81.91. While the average result of the students' post-test score was 97.35. From the specified categories, this research has reached the category of success, indicators of success of student biology learning outcomes or the average value of student learning outcomes, namely fulfilling the KKM, namely 75. Based on this, it can be concluded that the application of discovery learning learning models improves student biology learning outcomes class XI MIPA 2 SMA Negeri 11 Denpasar for the academic year 2022/2023.